Rising school attendance in rural India: an evaluation of the effects of major educational reforms. Issue 2 (4th March 2018) - Datta Gupta, Nabanita; Dubey, Amaresh; Simonsen, Marianne
ABSTRACT: We evaluate the impact of educational reforms starting from the mid-1990s in India on the school attendance rate of low-income rural children aged 6–14 compared to ineligible rural children, employing NSSO data from 1983 to 2004/2005. We estimate a triple difference model allowing for differential (linear) trends and find a positive causal effect of school reforms on the school attendance rate of rural low-income children, although somewhat stronger for girls than boys. For both girls and boys in these groups, the increase in attendance rate is driven by the 6–11 age category and by children of scheduled tribe or scheduled caste background.